Electrochemical Catalytic Behavior of Cu2O Catalyst for Oxygen Reduction Reaction in Molten Carbonate Fuel Cells - Song, Shin Ae; Kim, Kiyoung; Lim, Sung Nam; Han, Jonghee; Yoon, Sung Pil; Kang, Min-Goo; Jang, Seong-Cheol (KOREAN ELECTROCHEMISTRY SOC, 2018)
To enhance the performance of cathodes at low temperatures, a Cu-coated cathode is prepared, and its electrochemical performance is examined by testing its use in a single cell. At 620 degrees C and a current density of 150 mAcm(-2), a single cell containing the Cu-coated cathode has a significantly higher voltage (0.87 V) during the initial operation than does that with an uncoated cathode (0.79 V). According to EIS analysis, the high voltage of the cell with the Cu-coated cathode is due to the dramatic decrease in the high-frequency resistance related to electrochemical reactions. From XPS analysis, it is confirmed that the Cu is initially in the form of Cu2O and is converted into CuO after 150 h of operation, without any change in the state of the Ni or Li. Therefore, the high initial cell voltage is confirmed to be due to Cu2O. Because Cu2O is catalytically active toward O-2 adsorption and dissociation, Cu2O on a NiO cathode enhances cell performance and reduces cathode polarization. However, the cell with the Cu-coated cathode does not maintain its high voltage because Cu2O is oxidized to CuO, which demonstrates similar catalytic activity toward O-2 as NiO.
Keywords: LONG-TERM OPERATION; ELECTRODE PERFORMANCE; DIMETHYL CARBONATE; COATED CATHODE; OXIDATION; ANODE; NANOPARTICLES; TEMPERATURE; NICKEL; COPPER